Analysing the role of fintech and resource use in shaping environmental outcomes using load capacity factor in G20 countries - Harshita Jangid; Navuluru Venkata Muralidhar Rao; Debi Prasad Bal (Discover Sustainability)
Abstract This study examines the dynamic interrelationships between financial technology (fintech), natural resource rents, economic growth, urbanization, and environmental sustainability, using the Load Capacity Factor (LCF) as a composite measure of ecological balance. Unlike prior studies that rely solely on demand-side indicators such as carbon emissions or ecological footprint, this research employs LCF to capture both environmental supply and demand dimensions. Utilizing annual data spanning from 2005 to 2022, we construct fintech index using variables, namely, automated teller machine, mobile cellular subscription, fixed broadband subscription, and internet usage, by employing Principal Component Analysis approach. For preliminary testing, current study considers cross-sectional dependency test, slope homogeneity tests, pedroni and westerlund tests for cointegration and pairwise dumitrescu hurlin panel granger causality tests, and common correlated effects mean group and driscoll-kraay estimation for robustness. For result findings, we utilized the panel Vector Autoregression (Panel-VAR) method to illustrate the dynamic relationships among these variables. Our findings from Panel VAR approach indicate that fintech shocks initially have a positive impact on natural resource rent and load capacity factor but this effect weakens over later horizon, suggesting the need for cautious policy design. Furthermore, economic growth responds positively to fintech shocks, while the influence of fintech on natural resource rent and urbanization appears to be negative. From a policy standpoint, our research suggests that promoting fintech could mitigate environmental degradation and contribute to sustainable development. Graphical abstract